Observation of motorcycle helmet use rates in Michigan after partial repeal of the universal motorcycle helmet law. (October 2016) - Buckley, Lisa; Bingham, C. Raymond; Flannagan, Carol A.; Carter, Patrick M.; Almani, Farideh; Cicchino, Jessica B.
Highlights: Helmet use rates from crash record data was 73% in Michigan. Estimated state use was 75%, adjusted for roadway, motorcycle class, and time of day. After the partial repeal of Michigan's universal motorcycle helmet law use has declined. Abstract: Motorcycle crashes result in a significant health burden, including many fatal injuries and serious non-fatal head injuries. Helmets are highly effective in preventing such trauma, and jurisdictions that require helmet use of all motorcyclists have higher rates of helmet use and lower rates of head injuries among motorcyclists. The current study examines helmet use and characteristics of helmeted operators and their riding conditions in Michigan, following a weakening of the state's universal motorcycle helmet use law in April 2012. Data on police-reported crashes occurring during 2012–14 and from a stratified roadside observational survey undertaken in Southeast Michigan during May-September 2014 were used to estimate statewide helmet use rates. Observed helmet use was more common among operators of sports motorcycles, on freeways, and in the morning, and least common among operators of cruisers, on minor arterials, and in the afternoon. The rate of helmet use across the state was estimated at 75%, adjusted for roadway type, motorcycle class, and time of day. Similarly, the helmet use rate found from examination of crash records was 73%. In the observation survey, 47% of operators wore jackets, 94% wore long pants, 54% wore boots, and 80% wore gloves. Protective clothing of jackets and gloves was most often worn by sport motorcycle operators and long pants and boots most often by riders of touring motorcycles. Findings highlight the much lower rate of helmet use in Michigan compared with states that have a universal helmet use law, although the rate is higher than observed in many states with partial helmet laws. Targeted interventions aimed at specific groups of motorcyclists and situations where helmet use rates are particularly low should be considered to increase helmet use.